Spontaneous Haemomediastinum and Fatal Haemoperitoneum in woman with Vascular Ehlers-Danlos Syndrome - Isabel Cal; Elena Fernández; Jose V Méndez; Jose R Jarabo (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Abstract: Vascular Ehlers-Danlos Syndrome (EDS) presents with fragility of blood vessels, with high incidence of fatal hemorrhages in middle-age adults. We present a 38-year old female with vascular EDS presented to  the  emergency  unit  with  spontaneous  hemomediastinum  and  hemothorax. A selective arteriography showed  a  bronchial  artery  aneurysm  that  could  be  embolized. Coagulated  hemothorax  was cleared up using intrapleural instillation of urokinase. Acute massive hemoperitoneum happened a few hours later, due  to  spontaneous  disruption  of  a  splenic  artery  aneurysm.  It  could  not  be  managed  and  led  to  the decease of the patient. Multifocal bleeding is a frequent threatening event in vascular EDS.